2017
DOI: 10.1111/1346-8138.13987
|View full text |Cite
|
Sign up to set email alerts
|

New onset or transition of disease state of psoriatic arthritis during treatment with ustekinumab: A single‐center retrospective study

Abstract: Ustekinumab (UST) is a treatment option for psoriatic arthritis (PsA), but recent observations indicate that some psoriatic patients may experience new onset of PsA or worsening of pre-existent PsA. We retrospectively analyzed all cases of psoriasis vulgaris (PsV) and PsA treated with UST in our facility between 2011 and 2015. PsA developed in eight out of 179 PsV patients, mostly later than 8 months after initiation of UST. It was generally not severe, and none had received tumor necrosis factor (TNF)-α inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…Reviewing the literature, characteristics that may strongly predict the development of PsA were not found, since there are very variable data. For example, the female prevalence reported by Van Muijen et al [23] is supported also by our results but not by Napolitano et al The correlation with body mass index suggested by Asahina et al [24] and the correlation with PASI showed by Napolitano et al [22] were not confirmed in the other studies.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…Reviewing the literature, characteristics that may strongly predict the development of PsA were not found, since there are very variable data. For example, the female prevalence reported by Van Muijen et al [23] is supported also by our results but not by Napolitano et al The correlation with body mass index suggested by Asahina et al [24] and the correlation with PASI showed by Napolitano et al [22] were not confirmed in the other studies.…”
Section: Discussionsupporting
confidence: 57%
“…Indeed, different studies [22][23][24]34] and real-life experiences [35][36][37][38][39][40][41][42] showed the possibility of PsA onset in patients treated with biologics for psoriasis in 4.5-9.4% of cases [22,24]. The present study aims to evaluate the incidence of new-onset PsA in patients with plaque psoriasis on anti-TNFα (adalimumab, certolizumab, etanercept, infliximab), anti-IL12/23 (ustekinumab), anti-IL23 (risankizumab, tildrakizumab, guselkumab) or anti-IL17 (brodalumab, ixekizumab, secukinumab) therapy attending our Dermatology Unit and undergoing at least 1-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations